STUDENTS’ ANXIETY IN SPEAKING OF HORTATORY EXPOSITION TEXT - Adisti Rahayu; Irsyad Nugraha; Yustika Nur Fajriah (Institut Pendidikan Indonesia Garut, 2019)
This study was aimed to identify types of anxiety in students’ speaking of hortatory exposition texts in one of universities in Garut. To achieve the aforementioned purpose, qualitative approach embracing case study was employed. The data were gathered through observation of the second graders’ speaking performances. The data were analyzed inductively that was transcribed, categorized, analyzed, interpreted and concluded. As the result, there are two types of speaking anxiety; they are trait anxiety and state/situational anxiety. Furthermore, this study suggests teachers be more creative in designing the teaching planning of speaking class.